Prognostic value of NFκB, CD9, and VEGF in gastrointestinal stromal tumors - Tasdemir, Arzu; Soyuer, Isin; Unal, Dilek; Artis, Tarik (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Gastrointestinal stromal tumors (GISTs) are the most frequent mesenchymal tumors of the gastrointestinal system. We aimed to determine whether nuclear transcription factor κB (NF-κB), CD9 and vascular endothelial growth factor (VEGF) have prognostic value in patients with GIST. Material and methods : Thirty-five patients with GIST, who were diagnosed in the Pathology Department of Erciyes University, were included in the study. Cases were classified based on the 2002 NIH consensus. CD9, VEGF, and NF-κB immunohistochemistry were applied to GIST cases positive for CD117 and CD34, which are used to evaluate GISTs immunohistochemically. Results: Although there are no statistically significant differences between NF-κB (p = 0.329), CD9 (p = 0.269), and VEGF (p = 0.372) and risk groups, 79.22% of cases that stained positive for NF-κB, 81% of cases that stained positive for CD9, and 80% of cases that stained positive of VEGF were in the high risk group. Conclusions : It was found that NF-κB, CD9, and VEGF, which are important in predicting behaviors of other malign tumors, were expressed at high rates in high risk group GISTs. This can be used to determine prognosis with tumor diameter, mitosis rate under 50 BBS, Ki-67 proliferation index and other parameters.